Global analysis by LC-MS/MS of N6-methyladenosine and inosine in mRNA reveal complex incidence - Stejskal, Stanislav; Rájecká, Veronika; Covelo-Molares, Helena; Sinigaglia, Ketty; Brožinová, Květoslava; Kašiarová, Linda; Dohnálková, Michaela; Reyes-Gutierrez, Paul Eduardo; Cahová, Hana; Keegan, Liam P; O'Connell, Mary A; Vaňáčová, Štěpánka (RNA (New York, N.Y.), 2025)
The precise and unambiguous detection and quantification of internal RNA modifications represents a critical step for understanding their physiological functions. The methods of direct RNA sequencing are quickly developing allowing for the precise location of internal RNA marks. This detection is, however, not quantitative and still presents detection limits. One of the biggest remaining challenges in the field is still the detection and quantification of m6A, m6Am, inosine, and m1A modifications of adenosine. The second intriguing and timely question remaining to be addressed is the extent to which individual marks are coregulated or potentially can affect each other. Here, we present a methodological approach to detect and quantify several key mRNA modifications in human total RNA and in mRNA, which is difficult to purify away from contaminating tRNA. We show that the adenosine demethylase FTO primarily targets m6Am marks in noncoding RNAs in HEK293T cells. Surprisingly, we observe little effect of FTO or ALKBH5 depletion on the m6A mRNA levels. Interestingly, the upregulation of ALKBH5 is accompanied by an increase in inosine level in overall mRNA.
Keywords: Inosine; FTO; chromatografie kapalinová; RNA Processing, Post-Transcriptional; inosin; Humans; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; adenosin; ADAR; AlkB Homolog 5, RNA Demethylase; Methylation; ALKBH5; kapalinová chromatografie-hmotnostní spektrometrie; tandemová hmotnostní spektrometrie; posttranskripční úpravy RNA; RNA editing; Tandem Mass Spectrometry; alfa-ketoglutarát-dependentní dioxygenasa, AlkB homolog 5; RNA, Messenger; Liquid Chromatography-Mass Spectrometry; Adenosine; metylace; HEK293 Cells; gen pro FTO; Chromatography, Liquid; inosine; lidé; HEK293 buňky; adenosine methylation; messenger RNA